O descumprimento contratual em tempos de COVID: uma análise da aplicação do Código Civil brasileiro e da Convenção das Nações Unidas sobre os Contratos de Compra e Venda Internacional de Mercadorias (CISG) - Araújo, Juliana Mascarenhas de (2023)
The present study aims to analyze and discuss a potential conflict between two legal frameworks - the Brazilian Civil Code and the United Nations Convention on Contracts for the International Sale of Goods (CISG) – in the context of the Covid-19 pandemic. Given the global changes caused by the pandemic, what are the impacts on private contracts regarding the possibilities of exemption from liability? To address this question, a bibliographic research will be conducted on the discussed topics, serving as a basis for qualitative research aimed at analyzing and discussing the qualification of contractual liability exemptions in the context of the pandemic, especially in the year 2021 in Brazil and worldwide. This analysis will take into account the peculiarities of each regulation and the effects of the legislation in each specific case. Initially, an analysis will be made of the Covid-19 pandemic and its economic consequences, which affect private contractual relationships. Then, the principles and relevant contractual clauses that could address this specific moment will be examined. Subsequently, the provisions of the Brazilian Civil Code and the CISG will be discussed. Based on the examined concepts and established premises, decisions regarding the application of the studied institutes in the context of the Covid-19 pandemic will be analyzed. However, unlike the many decisions applying the Brazilian Civil Code, we did not identified decisions based on article 79 of the CISG in the context of the Covid-19 pandemic, so we limited the analysis to a theoretical evaluation of the application of the article to the concrete case and proceeded to an analysis of concrete cases regarding the Brazilian Civil Code. After the analysis, we concluded that there is a very big difference between force majeure and hardship in the CISG and in the Brazilian Civil Code, especially considering that the historical moment in which the judges were involved may even have led to less technically grounded decisions in disputes, driven by social appeal